PD-L1 monoclonal antibody-conjugated nanoparticles enhance drug delivery level and chemotherapy efficacy in gastric cancer cells - Xu S (Dove Medical Press, 2018)
Shijie Xu,1,* Fangbo Cui,2,3,* Dafu Huang,4,* Dinghu Zhang,5 Anqing Zhu,6 Xia Sun,6 Yiming Cao,7 Sheng Ding,7 Yao Wang,7 Eryun Gao,3 Fenglin Zhang3 1Center for Public Health Research, Medical School, Nanjing University, Nanjing, China; 2Department of Oncology, Wannan Medical College, Wuhu, Anhui, China; 3Department of Oncology, The People’s Hospital of Ma Anshan, Ma Anshan, Anhui, China; 4Department of Oncology, Nanjing Lishui People’s Hospital, Zhongda Hospital Lishui Branch, Southeast University, Nanjing, Jiangsu, China; 5Department of Oncology, Tongde Hospital of Zhejiang Province, Hangzhou, China; 6Department of Oncology, The Affliated Jiangyin Hospital of Southeast University Medical College, Jiangyin, Jiangsu, China; 7Department of General Surgery, The People’s Hospital of Ma Anshan, Ma Anshan, Anhui, China *These authors contributed equally to this work Background: Docetaxel (DOC) is widely used as a chemotherapy drug for various tumors, including gastric cancer (GC), but the clinical application of DOC has been limited due to the hydrophobicity of the drug. We aimed to formulate a multifunctional nanoparticle (NP) system to reduce the side effects of the chemotherapy agent, to promote synergistic therapeutic effects, and to achieve targeted delivery of the therapy. Methods: The polyethylene glycol-poly(ε-caprolactone) NPs (PEG-PCL NPs) were prepared by a ring opening copolymerization technique and were then conjugated with a programmed death-ligand 1 (PD-L1) monoclonal antibody (mAb). The effects of the surface coating on particle size, size distribution, zeta potential, drug encapsulation efficiency, loading capacity, and the drug release kinetics were investigated. By using a panel of PD-L1-expressing human GC cell lines and PD-L1-overexpressing cells, we studied cellular uptake, cytotoxic effects, and cellular apoptosis in the presence of PD-L1 mAb-conjugated NPs. Results: The characterization of the structure and biological functions of DOC-PEG-PCL-mAb NPs was investigated in vitro. X-ray photoelectron spectroscopy validated the presence of the PD-L1 mAbs on the NP surface. The cellular uptake analysis showed that the antibody-conjugated NPs achieved significantly higher cellular uptake. The results of an in vitro cytotoxicity experiment on three GC lines further proved the targeting effects of the antibody conjugation. In addition, we found that the DOC-PEG-PCL-mAb NPs induced cell apoptosis and enhanced G2-M arrest in cancer cells, indicating the inhibition of microtubule synthesis. When compared with the control groups, DOC-PEG-PCL-mAb NPs are more effective in inhibiting PD-L1 expression in GC cells. Conclusion: Our results reported here highlight the biological and clinical potential of DOC-PEG-PCL-mAb NPs using PD-L1 mAbs in GC treatment. Keywords: DOC, gastric carcinoma, PD-L1 monoclonal antibody, nanomedicine, drug delivery